Students’ willingness to attend EFL classes with respect to teachers’ credibility, stroke, and success: A cross-cultural study of Iranian and Iraqi students’ perceptions - Pishghadam, Reza; Derakhshan, Ali; Zhaleh, Kiyana; Al-Obaydi, Liqqa Habeb (Current psychology (New Brunswick, N.J.), 2023)
We investigated the home culture effect with respect to students’ perceptions about themselves and their instructors. This study was concerned with the cross-cultural analysis of Iranian and Iraqi students’ perceptions of teacher success, credibility, and stroke variables. Willingness to Attend Classes (WTAC) was evaluated. Two-hundred-seventy-six Iranian and 150 Iraqi English as a Foreign Language (EFL) university students participated in the study. Results of the multi-group modeling showed measurement invariance, both metric and scalar, across the groups. Afterwards, descriptive statistics indicated that both groups held high perceptions of their own WTAC and their teachers’ stroke, effectiveness, and credibility. Next, correlational results indicated that the sub-components of perceived teacher credibility, stroke, and success variables were significantly and positively associated with Iranian and Iraqi students’ WTAC. These outputs were approved in the SEM results, and the hypothesized relations between the variables were approved; perceived teacher stroke, success, and credibility factors were positive significant predictors of Iranian and Iraqi students’ WTAC. On the whole, these findings provided empirical backing for the theoretically-rich claim that students’ home culture background significantly predicts the way their belief systems are shaped and reshaped. Hence, teacher educators should be concerned with training teachers who not only effectively teach language to the students but also fulfill students’ expectations of a successful teacher who is able to provide culturally-appropriate quality communication in the classroom and build a relationship of trust between him/herself and the students with the ultimate aim of enhancing student-related academic outcomes.